STRATEGI GURU DALAM MENINGKATKAN PEMAHAMAN FIQIH PADA PESERTA DIDIK - Yely Wulandari; Sudianto (CV. ADIBA AISHA AMIRA, 2026)
Learning strategy is a series of planned activities that include methods, techniques, and the utilization of instructional media designed systematically to achieve educational objectives. This study aims to describe teachers’ strategies in improving students’ understanding in Fiqh subjects. The research problem focuses on how teachers implement strategies to enhance students’ comprehension of Fiqh. This study employs a qualitative approach with a library research design. Data were obtained through literature review and analysis of relevant books, scientific journals, and academic documents. The findings indicate that, based on the literature, improving students’ understanding begins with the preparation of Lesson Plans (RPP), the preparation of learning materials and media, and the selection of appropriate approaches, models, and methods aligned with students’ characteristics and classroom conditions. Effective learning interaction positions the teacher as an educator, mentor, and role model for students.